Open innovation for sustainability in the social enterprises: An empirical evidence - Budi Harsanto; Asep Mulyana; Yudi Ahmad Faisal; Venny Mellandhia Shandy (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Social enterprises are currently receiving significant attention from academics and practitioners because of their hybrid nature to achieve profit while achieving the planned social mission. To achieve their social mission as well as financial sustainability, social enterprises need to have the ability to carry out innovation for sustainability which helps them balance these two goals. In hybrid organizations, such as social enterprises, priorities in financial and social missions may conflict, resulting in managerial tensions and stakeholder pressure, making open innovation (OI) by involving external parties essential. This paper aims to explore OI for sustainability in social enterprises. The research question posed is: what innovation for sustainability practices do social enterprises implement and, how does the mechanism of OI for sustainability work in social enterprises? A multiple case study approach is used by taking four leading social enterprises in the education sector located in West Java, Indonesia. Our findings indicate that sustainability innovation is practiced by social enterprises in the form of providing social benefits such as paying for the education costs of their students and providing social services for the surrounding community. Beyond that, ecological benefits are provided in the form of reducing waste and using unproductive land in a productive manner. Innovation is performed with a different approach from one case to another. All cases studied collaborate with parties external to the organization to be able to implement sustainability innovation. This study contributes to the literature by providing empirical research on sustainability innovation in the context of social enterprises, which is still rarely found in the literature.
Keywords: 650; open innovation; case study; education; social enterprises; sustainability innovation